Vitamin A Supplementation Was Associated with Reduced Mortality in Patients with Ebola Virus Disease during the West African Outbreak. Issue 10 (3rd July 2019) - Aluisio, Adam R; Perera, Shiromi M; Yam, Derrick; Garbern, Stephanie; Peters, Jillian L; Abel, Logan; Cho, Daniel K; Kennedy, Stephen B; Massaquoi, Moses; Sahr, Foday; Brinkmann, Suzanne; Locks, Lindsey; et al.
ABSTRACT: Background: Micronutrient supplementation is recommended in Ebola virus disease (EVD); however, there are limited data on therapeutic impacts of specific micronutrients. Objective: To evaluate the association between vitamin A supplementation and mortality in EVD. Methods: This retrospective cohort included patients with EVD admitted to 5 International Medical Corps Ebola Treatment Units (ETUs) in 2 countries during 2014–2015. Protocolized treatments with micronutrients were used at all ETUs: however, because of resource constraints, only a subset of patients received vitamin A. Standardized data on demographics, clinical characteristics, malaria status, and Ebola viral loads (cycle threshold values) were collected. The outcome of interest was mortality between cases treated with 200, 000 IU of vitamin A on care days 1 and/or 2, and those not. Propensity scores based on the first 48 h of care were derived using covariates of age, ETU duration, malaria status, cycle threshold values, and clinical symptoms. Patients were matched 1:1 using nearest neighbors with replacement. Mortality between cases treated and not treated with vitamin A was compared using generalized estimating equations to calculate RR with associated 95% CI. Results: There were 424 cases analyzed, of which 330 (77.8%) were treated with vitamin A. The mean age was 30.5 y and 40.3% were men. The most common symptoms were diarrhea (85.6%), anorexia (80.7%), and abdominal pain (76.9%). Mortality proportions among cases treated and not treated with vitamin A were 55.0% and 71.9%, respectively. In the propensity-matched analysis, mortality was significantly lower among cases receiving vitamin A (RR = 0.77, 95% CI: 0.59, 0.99; P = 0.041). In a subgroup analysis of patients treated with multivitamins already containing vitamin A, additional vitamin A supplementation did not impact mortality. Conclusion: Early vitamin A supplementation was associated with reduced mortality in patients with EVD, and should be further studied and considered for use in future epidemics.